Analisis Persepsi Petani Terhadap Penggunaan Benih Bawang Merah Varietas Gayo Dan Varietas Batu Ijo Di Kecamatan Lut Tawar Kabupaten Aceh Tengah - Andriani, Dini; Mardhiah, Ainal; Khumaira, Khumaira (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
Shallot farming in Laut Tawar District is on the outskirts of Lake Lut Tawar by utilizing land on the edge of the lake. This study aims to determine the perception of farmers who use Gayo and Batu Ijo seeds towards the use of shallot seeds in Lut Tawar District, Central Aceh Regency, as well as to find out the difference in farmers' perception of the use of Gayo and Batu Ijo shallot seeds. The Data Analysis model used was Likert skla analysis and Mann Whitney analysis. The results of the study showed that farmers who used Batu Ijo shallot seeds were in the good category with a score of 3.73 and farmers who used Gayo shallot seeds were in the good category with a score of 3.71 and based on the results of the differential test obtained, there was no significant difference in perception of the use of Batu Ijo shallot seeds and Gayo varieties.